The Role of the Principal in Educational Marketing Management at Public High Schools - Siti Nur Halimah; Sya'roni Ma'shum (International Journal of Advanced Studies in Educational Management (IJASEM), 2025)
This study aims to analyze the principal’s role in implementing educational marketing management at SMA Negeri 1 Pare, Kediri. The research was motivated by the increasing competition among schools in Pare District and the continuous growth in student enrollment at SMA Negeri 1 Pare. This study employed a qualitative descriptive approach with data collected through observation, documentation, and in-depth interviews with the principal and vice principals for public relations and student affairs. Data were analyzed using an interactive model consisting of data reduction, presentation, and conclusion drawing, supported by triangulation techniques to ensure validity. The findings revealed that the principal played a central role in marketing management through five main functions: planning, organizing, implementing, supervising, and evaluating marketing programs. Strategic steps included forming a marketing committee, involving teachers in promotional activities, utilizing social media, and maintaining partnerships with the community. These efforts successfully enhanced the school’s image and competitiveness. This study contributes to the understanding of leadership roles in educational marketing and provides a practical model for other public schools to strengthen their market position.